"Pure by NMR"? - Claridge, T; Davies, S; Polywka, M; Roberts, P; Russell, A; Savory, E; Smith, A (2008)
Integration of a (13)C-(1)H satellite peak of a given (12)C-(1)H parent resonance within a quantitative (1)H NMR spectrum and comparison to the minor component represents a simple protocol for the accurate determination of diastereoisomeric ratios of up to 1000:1 (i.e., 99.8% de).